1998
DOI: 10.1046/j.1432-1327.1998.2520162.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of the Mig1p repressor by Snf1p‐dependent phosphorylation in the absence of glucose

Abstract: Mig1p, a zinc-finger protein that is related to the Krox/Egr, Wilms' tumor and Sp1 proteins, mediates glucose repression in the yeast Saccharomyces cerevisiae. Mig1p is inactive in the absence of glucose, and this inhibition is dependent on the Snf1p (Cat1p) protein kinase. The regulation is mediated by an internal part of Mig1p, and it can be transferred to a Mig1-viral protein 16 (VP16) fusion protein that functions as an activator [Östling, J., Carlberg, M. & Ronne, H. (1996) Mol. Cell. Biol. 16, 753Ϫ761]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 6 publications
4
95
0
Order By: Relevance
“…In particular, the SNF1 gene, which encodes a protein serine/threonine kinase, is essential for glucose repression (Celenza and Carlson, 1986). It forms a high molecular mass protein kinase complex that, upon removal of glucose, phosphorylates and thereby inactivates a DNA binding protein (Mig1) that represses transcription of glucose-repressed genes (Ostling and Ronne, 1998). Plant homologs of SNF1, called SNF1-related protein kinases 1s (SnRK1), which complement snf1 yeast mutants, have been identified (Alderson et al, 1991;Muranaka et al, 1994;Halford and Hardie, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the SNF1 gene, which encodes a protein serine/threonine kinase, is essential for glucose repression (Celenza and Carlson, 1986). It forms a high molecular mass protein kinase complex that, upon removal of glucose, phosphorylates and thereby inactivates a DNA binding protein (Mig1) that represses transcription of glucose-repressed genes (Ostling and Ronne, 1998). Plant homologs of SNF1, called SNF1-related protein kinases 1s (SnRK1), which complement snf1 yeast mutants, have been identified (Alderson et al, 1991;Muranaka et al, 1994;Halford and Hardie, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the snf1⌬ mutant, LexA-Sin4 and LexA-Srb11 levels remained nearly constant, but ␤-galactosidase activity did not increase. Control experiments with a mig1⌬ mutant showed that the effect is independent of the glucose-and Snf1-regulated transcriptional repressor Mig1 (19,21), thereby excluding any significant role for Mig1 in regulating this reporter. Thus, these findings indicate that the Snf1 kinase stimulates transcription by holoenzyme that has been recruited to a promoter (Fig.…”
Section: Snf1 Kinase Increases Transcription By Rna Polymerase II Holmentioning
confidence: 94%
“…Other Methods-Treatment with calf intestine phosphatase was performed as previously described (44). Briefly, 5 l of purified holo-RNA polymerase II was incubated at 37°C for 1 h in the presence or absence of calf intestine phosphatase (40 units).…”
Section: Methodsmentioning
confidence: 99%